Dirty, filthy cities: Australian crime films and cultural contexts in Melbourne and Sydney. (3rd October 2022) - Ellison, Elizabeth
Abstract: Australia is a country of extreme landscapes: untamed natural coastlines through to the mysterious and dangerous interior. Australian cinema has regularly showcased the country's landscape, often creating a sense of character in the land itself. Although the majority of Australians live in the major metropolitan hubs of the country, cities in cinema lose distinctiveness on-screen to augment opportunities for international success. However, two cities can be considered as having strong identities that are present on film: Melbourne and Sydney. By examining a selection of films that are specifically linked to these locations, this article suggests the crime genre has identified and captured challenging trends in these cities' recent histories: racial tension from increased diversity and multiculturalism in Australia's urban centres, declining confidence in law enforcement and police corruption, and high levels of dangerous drug use. This article will closely examine four films: Romper Stomper (Geoffrey Wright, 1992 ), Animal Kingdom (David Michôd, 2010 ), Felony (Matthew Saville, 2013 ) and Little Fish (Rowan Woods, 2005 ).